O erotismo dos hereges : análise da moral sexual dos cristãos-novos - Santana, Nilton Bruno Feitosa (2017)
The work presented here focus on the sexual morality of New Christians in New Spain. From the processes of the Spanish Inquisition will be analyzed the ritual of the Cro, which consisted of fasting with sexual relations and that had a direct connection with the religiosity of the new Christian Crypto-Jew. The new Christian was born at the time when the Catholic Kings of Castile decreed the forced conversion of the Jews who are in their dominions. This will develop numerous forms of religiosity through inquisitorial persecution, one of them will be practicing Judaism in a hidden way, later called crypto-Judaism. The ritual of the Cro is part of the crypto-Jewish religiosity born in the Ibero-American world, and just because it has the presence of sexual relations in the middle of religious rites, would already put it as a strange custom for the Christian culture and the Jewish customs that Developed far from the inquisitorial fury. In order to observe the ritual of Cro, we will use the concept of Erotic Capital in order to observe the social implications it had within the new Christian community in Mexico City. It consists of elements that will be used to discover how the New Christian built his erotic capital using this unique ritual. It will be observed which elements were used to denote greater importance within the social group and in what kind of religiosity would fit the Cro within categories of social sciences. Christian-young sexual morality can very much tell us about what was considered a sexual crime by the institutions of the Iberian world and its possessions.